Multidimensional Analysis of CHMP Family Members in Hepatocellular Carcinoma - Guo Y; Shang A; Wang S; Wang M (International Journal of General Medicine, 2022)
Yu Guo,1 An Shang,1 Shuang Wang,2 Min Wang1 1Department of General Surgery, Jilin University Second Hospital, Changchun, Jilin, People’s Republic of China; 2Department of Dermatology, Jilin University Second Hospital, Changchun, Jilin, People’s Republic of ChinaCorrespondence: Shuang Wang, Department of Dermatology, Jilin University Second Hospital, 218 Ziqiang Street, Nanguan District, Changchun, Jilin, People’s Republic of China, Tel +86-181-3543-5372, Email jdeywangshuang@163.comBackground: EGFR frequently accumulates and mutates simultaneously in various cancers. Ubiquitinated EGFR proteins can be degraded by the endosomal sorting complex required for transport. Among them, ESCRTIII is mainly composed of CHMP family members.Methods: A total of 424 samples from the TCGA-LIHC data set were used to explore the relationship between CHMPs and liver hepatocellular carcinoma (LIHC). Oncomine, the Human Protein Altas, cBioPortal, TISIDB, TIMER, Metascape, and R software were used to facilitate analysis of the role played by CHMPs in the pathogenesis of LIHC. The role of CHMPs in the development of LIHC was analyzed in terms of differential expression, survival, mutation, immunoinfiltration, functional enrichment, and drug sensitivity.Results: Differential expression analysis showed that CHMPs were significantly more expressed in LIHC tumor tissue, and the high expression of some CHMPs was closely correlated with clinicopathological stage. The prognosis was worse in the group with high expression of CHMPs. Among them, CHMP4C was considered to play a major role. Gene-mutation analysis and DNA promoter–methylation analysis further revealed possible mechanisms for the aberrant amplification of CHMPs. Immunoinfiltration analysis indicated that CHMPs were closely associated with multiple immune cells and exhibited resistance to various drugs when highly expressed.Conclusion: CHMPs were found to be significantly elevated in LIHC and strongly associated with immune-cell infiltration, poor prognosis, multiple star pathways, and drug resistance.Keywords: hepatocellular carcinoma, ESCRT, EGFR, CHMP4C